2013
DOI: 10.1159/000346550
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Membrane Vesicles in Secretion of <b><i>Lysobacter</i></b> sp. Bacteriolytic Enzymes

Abstract: Membrane vesicles produced by bacteria have been intensively studied in the recent years. Investigators have noted their roles in essential processes in the bacterial cell including secretion of proteins by the ‘eukaryotic' vesicular mechanism. To date, formation of vesicles is not considered to be a spontaneous event. Many believe it to be a programmed process that can be guided by several mechanisms. Vesicles are derivatives of the cell envelope, which in turn is a supramolecular structure where the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Vesicles containing this enzyme possess a lytic activity against the autoclaved cells of S. aureus 209P and the living cells of E. caratovora B15 [Vasilyeva et al, 2008[Vasilyeva et al, , 2013. In the present work, the lytic action of Lysobacter sp.…”
Section: Antimicrobial Spectrum Of Lysobacter Sp Xl1 Vesicles Contaimentioning
confidence: 51%
See 3 more Smart Citations
“…Vesicles containing this enzyme possess a lytic activity against the autoclaved cells of S. aureus 209P and the living cells of E. caratovora B15 [Vasilyeva et al, 2008[Vasilyeva et al, , 2013. In the present work, the lytic action of Lysobacter sp.…”
Section: Antimicrobial Spectrum Of Lysobacter Sp Xl1 Vesicles Contaimentioning
confidence: 51%
“…We found that the lytic action of Lysobacter sp. XL1 vesicles is due to the action of not autolytic but extracellular lytic enzymes [Vasilyeva et al, 2008[Vasilyeva et al, , 2013. The lytic action of vesicles on Grampositive bacteria was much stronger than on Gram-negative ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, bacteria are known which appear to possess membranous nuclear envelopes superficially resembling eukaryotic nuclei [Fuerst and Sagulenko, 2013]. Further, outer membrane vesicles of Gram-negative bacteria are now known to function in communication, protection and pathogenesis although such vesicular structures were thought to be largely limited to eukaryotes just a few years ago [Manning and Kuehn, 2013; Schertzer and Whiteley, 2013; Vasilyeva et al, 2013]. Finally, some intracellular organelles such as acidocalcisomes are ubiquitous, being present in bacteria, archaea and eukaryotes [Caetano-Anolles and Seufferheld, 2013].…”
Section: Introductionmentioning
confidence: 99%